10 key principles for successful solar air conditioning design – A compendium of IEA SHC Task 48 experiences. (15th September 2018) - Neyer, Daniel; Ostheimer, Manuel; Mugnier, Daniel; White, Stephen
Highlights: Experiences of research and demonstration activities were selected and summarized. Based on that 10 qualitative key principles were expressed within the IEA SHC Task 48. Background information and recent literature explain the rationales behind. A survey about the validity and importance of the principles was conducted. Essential, important and controversial principles can support the design of SHC plants. Abstract: The results of past and ongoing activities, in successive IEA SHC (solar heating and cooling) Tasks, suggest enormous potential for solar cooling technologies to reduce greenhouse gas emissions. However, solar thermal cooling still faces barriers to emerge as an economically competitive solution. IEA SHC Task 48 was introduced to gather learnings from existing installations, and to find technological and market solutions, which could enable industry to deliver solar thermal driven heating and cooling systems that are efficient, reliable and cost competitive. The selected experiences of these research activities were clustered into 10 qualitative key principles for successful design and operation of SHC systems. Three existing systems are fully discussed in a solar cooling design guide (Mugnier et al., 2017). This paper aims to introduce these key principles in its general format. The background to the qualitative statements is explained, supplemented with examples from the context of Task 48 and compared with recent literature. Furthermore, a survey was conducted among SHC experts, who provide an assessment of the importance of the principles. The result shows that all principles have their eligibility. However, it turns out that there are three main categories of principles: (i) essential, (ii) important and (iii) controversial. Following the key principles is not a guarantee, but they can support researchers, designers and contractors to implement solar heating and cooling systems successfully.